Embriogénesis gamética para obtención de haploides en alcornoque. - Bueno, A; GÓMEZ, A; Boscaiu, M; Manzanera, J A; Vicente, O (II Congreso Forestal Español, 1997)
Inducción of haploid embryos and regeneration of plantlets have been obtained for the first time, in cork oak (Quercus suber L.) by combining a starvation treatment in anther culture with a mild heat shock at 33°C for 5 days, followed by culture at 25°C in a simple agar medium without growth regulator.s. The same conditions had been shown previously to be optimal for embryogenic induction in isolated microspore cultures of several model species such as tobacco and wheat. These results support the notion that stress, particularly sucrose starvation, a heat shock or a combination of both treatments could be the major and general signal responsible for the inhibition of normal gametophytic development of the microspores and for the induction of the alternative embryogenic pathway. A similar approach may be used for the production of haploid and doubled haploids for plant breeding in other species that like most forest trees, are still recalcitrant in anther culture.
Keywords: anther culture; Cork oak; Haploid plants; Stress

Embriogénesis gamética para obtención de haploides en alcornoque. - Bueno, A.; GÓMEZ, A.; Boscaiu, M.; Manzanera, J. A.; Vicente, O. (II Congreso Forestal Español, 1997)
Inducción of haploid embryos and regeneration of plantlets have been obtained for the first time, in cork oak (Quercus suber L.) by combining a starvation treatment in anther culture with a mild heat shock at 33°C for 5 days, followed by culture at 25°C in a simple agar medium without growth regulator.s. The same conditions had been shown previously to be optimal for embryogenic induction in isolated microspore cultures of several model species such as tobacco and wheat. These results support the notion that stress, particularly sucrose starvation, a heat shock or a combination of both treatments could be the major and general signal responsible for the inhibition of normal gametophytic development of the microspores and for the induction of the alternative embryogenic pathway. A similar approach may be used for the production of haploid and doubled haploids for plant breeding in other species that like most forest trees, are still recalcitrant in anther culture.
The following values have no corresponding Zotero field: periodical: II Congreso Forestal Español pub-location: Pamplona
Keywords: anther culture; Cork oak; Haploid plants; Stress

Stress-induced formation of haploid plants through anther culture in cork oak (Quercus suber) - Bueno, Maria Angeles; Gomez, Arancha; Boscaiu, Monica; Manzanera, Jose Antonio; Vicente, Oscar (Physiologia Plantarum, 1997)
Induetion of haploid embryos and regeneration of plantlets have been obtained, for the first time, in cork oak (Quercus suber L.) by combining a starvation treatment in anther culture with a mild heat shock at 33°C for 5 days, followed by eulture at 25°C in a simple agar medium without growth regulators. The same conditions had been shown previously to be optimal for embryogenic induction in isolated microspore cultures of' several model species such as tobacco and wheat. These results support the notion that stress, particularly sucrose starvation, a heat shock or a combination of both treatments could be the major and general signal responsible for the inhibition of normal gametophytie development of the mierospores and for the induetion of the alternative embryogenic pathway. A similar approach may be used for the production of haploid and doubled haploids for plant breeding in other species that, like most forest trees, are still recalcitrant in anther culture.
Keywords: anther culture; Cork oak; flow cytometry; Haploid plants; heat shock; Quercus suber; starvation; Stress

Stress-induced formation of haploid plants through anther culture in cork oak (Quercus suber) - Bueno, Maria Angeles; Gomez, Arancha; Boscaiu, Monica; Manzanera, Jose Antonio; Vicente, Oscar (Physiologia Plantarum, 1997)
Induetion of haploid embryos and regeneration of plantlets have been obtained, for the first time, in cork oak (Quercus suber L.) by combining a starvation treatment in anther culture with a mild heat shock at 33°C for 5 days, followed by eulture at 25°C in a simple agar medium without growth regulators. The same conditions had been shown previously to be optimal for embryogenic induction in isolated microspore cultures of' several model species such as tobacco and wheat. These results support the notion that stress, particularly sucrose starvation, a heat shock or a combination of both treatments could be the major and general signal responsible for the inhibition of normal gametophytie development of the mierospores and for the induetion of the alternative embryogenic pathway. A similar approach may be used for the production of haploid and doubled haploids for plant breeding in other species that, like most forest trees, are still recalcitrant in anther culture.
Keywords: anther culture; Cork oak; flow cytometry; Haploid plants; heat shock; Quercus suber; starvation; Stress